Analisis Campur Kode Pada Lirik Lagu “By My Side” Dipopulerkan Oleh Maudy Ayunda Dan David Choi - Maguna Eliastuti; Ambar Dalagati; Ratna Widianti; Khasina Fitri; Muhammad Andi Maulana (Pusat riset dan Inovasi Nasional, 2023)
Song lyrics are a series of words that form a song, consisting of several stanzas, refrains or choruses. Forming song lyrics is not as easy as compiling an essay, but it can be obtained in the form of one's expression such as experiences that have been experienced, things that have been seen or heard, and various inspirations. The writer will express his experience by doing word games and language so as to create interest and distinctiveness in the lyrics or verses. This research is qualitative research and uses qualitative descriptive methods, namely interpreting and describing data. The main object of his research was the song